2015
DOI: 10.1523/jneurosci.4518-13.2015
|View full text |Cite|
|
Sign up to set email alerts
|

Use-Dependent Activation of Neuronal Kv1.2 Channel Complexes

Abstract: In excitable cells, ion channels are frequently challenged by repetitive stimuli, and their responses shape cellular behavior by regulating the duration and termination of bursts of action potentials. We have investigated the behavior of Shaker family voltage-gated potassium (Kv) channels subjected to repetitive stimuli, with a particular focus on Kv1.2. Genetic deletion of this subunit results in complete mortality within 2 weeks of birth in mice, highlighting a critical physiological role for Kv1.2. Kv1.2 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 44 publications
6
42
0
Order By: Relevance
“…depolarizing shift in the half-maximal activation (Watanabe et al, 2007). Typical features of Kv1.2 are the low threshold (below action potential threshold) and the use-dependent activation (Baronas et al, 2015). Thus, Kv1.2 is activated before the action potential is elicited, and repetitive firing may increase Kv1.2 contribution to AP repolarization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…depolarizing shift in the half-maximal activation (Watanabe et al, 2007). Typical features of Kv1.2 are the low threshold (below action potential threshold) and the use-dependent activation (Baronas et al, 2015). Thus, Kv1.2 is activated before the action potential is elicited, and repetitive firing may increase Kv1.2 contribution to AP repolarization.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kv1.2 channels can be divided into slow and fast gating channels (Rezazadeh et al, 2007), and it is uncertain to what extent gating properties observed in expression systems can be transferred to presynaptic terminals. But for the dendritic Kv1.2 channels together with the use-dependent activation of Kv1.2 (Baronas et al, 2015), it is possible that the patient's antibody shifts the slow gating channel into the fast gating one. Interestingly, both loss-of-function and gain-of-function mutations of the Kv1.2-encoding gene, KCNA2, were associated with epileptic encephalopathy (Syrbe et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on prior observations of variable Kv1.2 function in different cell types, we hypothesized that Kv1.2 is influenced by a variety of unidentified regulators (Abraham et al, 2019;Baronas et al, 2017Baronas et al, , 2016Baronas et al, , 2015Rezazadeh et al, 2007) . We have pursued the identification of novel regulatory proteins that may influence this widely used model Kv channel.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has served as an essential structural template for the interpretation of functional data in a variety of ion channel types, and for the generation and simulation of in silico models of ion channels. Despite the understanding implied by the precision of an atomic resolution structure, there is remarkable variability of Kv1.2 gating behavior in different experimental reports and expression systems, suggesting a regulatory mechanism that has yet to be described 5 – 9 .…”
Section: Introductionmentioning
confidence: 99%